1999
DOI: 10.1289/ehp.99107745
|View full text |Cite
|
Sign up to set email alerts
|

Oil shale processing as a source of aquatic pollution: monitoring of the biologic effects in caged and feral freshwater fish.

Abstract: The biologic effects of the oil shale industry on caged rainbow trout (Oncorhynchus mykiss) as well as on feral perch (Perca fluviatilis) and roach (Rutilus rutilus) were studied in the River Narva in northeast Estonia. The River Narva passes the oil shale mining and processing area and thus receives elevated amounts of polycyclic aromatic hydrocarbons (PAHs), heavy metals, and sulfates. The effects of the chemical load were monitored by measuring cytochrome P4501A (CYP1A)-dependent monooxygenase (MO) activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Concerning phase II, our results seem in line with previous field studies that failed to observe any alteration in GST and UDPGT activities in fish resident in PAH-contaminated sites (for a review see van der Oost et al, 2003;Martínez-Gómez et al, 2009) although some evidence of inhibition of GST activity has been reported in fish from PAH-contaminated sites (Bagnasco et al, 1991;Tuvikene et al, 1999). The different trends observed for GST and UDPGT activities with respect to other parameters is somehow unexpected as GST and UDPGT are actively involved in cell detoxification and glutathione conjugates in particular are the preferential substrates of MRP2 (Leslie et al, 2005).…”
Section: Hissupporting
confidence: 92%
“…Concerning phase II, our results seem in line with previous field studies that failed to observe any alteration in GST and UDPGT activities in fish resident in PAH-contaminated sites (for a review see van der Oost et al, 2003;Martínez-Gómez et al, 2009) although some evidence of inhibition of GST activity has been reported in fish from PAH-contaminated sites (Bagnasco et al, 1991;Tuvikene et al, 1999). The different trends observed for GST and UDPGT activities with respect to other parameters is somehow unexpected as GST and UDPGT are actively involved in cell detoxification and glutathione conjugates in particular are the preferential substrates of MRP2 (Leslie et al, 2005).…”
Section: Hissupporting
confidence: 92%
“…SigniWcant decreases in GST activity were reported in rainbow trout exposed to TCDD (Hektoen, Bernloft, Ingebrigtsen, Skaare, & Goksøyr, 1994), sea bass and sunWsh exposed to PAH (Lemaire, Förlin, & Livingstone, 1996;Oikari & Jimenez, 1992); and also in Wsh species from polluted environments (Tuvikene et al, 1999;Otto et al, 1996). The GST liver activity did not show a clear correlation with levels of PAHs metabolites in bile.…”
Section: Discussionmentioning
confidence: 96%
“…Glutathionation is a step within the detoxiWcation of pollutants catalysed by GSTs. However, the data available are not consistent, with some reports indicating an increase in the enzyme activity in contrast with others that do not observe changes or even reported signiWcant decreases (Otto, Buttner, Arquette, & Moon, 1996;Tuvikene et al, 1999;Van der Oost et al, 2003). Mullet was chosen because it possesses several characteristics required in an estuarine bioindicator species, such as the extreme salinity tolerance, and also because it is very common in southern European estuarine systems, and therefore may be a good tool for monitoring programs (Ferreira et al, 2004, Ferreira, Moradas-Ferreira, & Reis-Henriques, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent research indicates oil shale wastes may cause little harm to fish (10), any water that washes off oil shale waste piles is now collected and purified, Aarna says. Electrostatic precipitation can cut the fly ash waste by more than 99%, but the country has only been able to install the technology on half of its 20 electricity-producing units, Aarna says.…”
Section: Reliance On a Very Dirty Fuelmentioning
confidence: 99%